The applicability of heat transfer correlations to flows in minichannels and new correlation for subcooled flow boiling. (September 2020) - Strąk, Kinga; Piasecka, Magdalena
Highlights: Steady-state flow boiling heat transfer in a single rectangular minichannel. Several refrigerants flowing in a different spatial oriented minichannel. Enhanced heated plate surface produced by several methods. Applicability of heat transfer correlations to flows in minichannels. New correlation for subcooled flow boiling heat transfer in minichannels. Abstract: This paper focuses on the applicability of heat transfer correlations to flows in minichannels. The data were taken from own research conducted at the experimental stand for subcooled flow boiling heat transfer in an asymmetrically heated rectangular minichannel oriented with seven inclination angles (0°, 30°, 60°, 90°, 120°, 150°, and 180°) relative to the horizontal plane. Various cooling liquids (FC-72, HFE-649, HFE-7100 or HFE-7000) flowing along a minichannel were heated by a thin plate. The plate had a smooth or enhanced surface on the side that was in contact with the fluid. The enhanced surfaces were obtained by vibration-assisted laser surface texturing or electromachining. Porous surfaces produced by soldering or sintering iron powder to the heated surface were also tested. Infrared thermography was used to determine changes in temperature on the outer smooth surface of the plate. Local heat transfer coefficients in the contact surface between the heated plate and the cooling fluid were determined using the one-dimensional mathematical method. A dozen or so heat transfer correlations selected from the literature have been used in calculations. It was found that the majority of correlations enabled the predicting of Nusselt number within error bands of ±25%. The smallest mean absolute percentage error in determining the Nusselt number was obtained using Mikielewicz J. correlation. A new correlation for subcooled flow boiling heat transfer in minichannels was proposed. The mean absolute percentage error of the Nusselt number, amount to 14%, was achieved according to own correlation.